Trading away incentives - Stefano Colonnello; Giuliano Antonio Curatola; Shuo Xia (Halle Institute for Economic Research (IWH), 2022)
Equity pay has been the primary component of managerial compensation packages at US public firms since the early 1990s. Using a comprehensive sample of top executives from 1992-2020, we estimate to what extent they trade firm equity held in their portfolios to neutralize increments in ownership due to annual equity pay. Executives accommodate ownership increases linked to options awards. Conversely, increases in stock holdings linked to option exercises and restricted stock grants are largely neutralized through comparable sales of unrestricted shares. Variation in stock trading responses across executives hardly appears to respond to diversification motives. From a theoretical standpoint, these results challenge (i) the common, generally implicit assumption that managers cannot undo their incentive packages, (ii) the standard modeling practice of treating different equity pay items homogeneously, and (iii) the often taken for granted crucial role of diversification motives in managers' portfolio choices.
Keywords: G32; G34; J33; M12; M52; 330; dynamic contracting; equity incentives; executive compensation; hedging; insider trading